Sosialisasi Penggunaan Lahan Sempit melalui Pemanfaatan Pekarangan Rumah di Desa Sirnagalih - Maudy Susanti; Nur Paisah Pasaribu; Wahyu Purwakusuma (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Sirnagalih Village is a village located relatively close to Bogor City, although it is still included in the area of Bogor Regency. The location is close to urban areas, making the social life of the people of Sirnagalih Village almost the same as urban areas. It was not only the condition of the community that was changing, but also the increase in infrastructure development felt by the villagers. This condition causes a reduction in green open space and land for agriculture. Land limitations can be overcome by optimizing the land around the house or yard. The purpose of this program is to provide awareness to the community to be able to utilize existing land optimally so that it can provide benefits to the environment (greening facilities). The program was carried out on Thursday 27 June 2019 in Sirnagalih Village and was divided into 2 stages, namely socialization and demonstration. The socialization was delivered to the representatives of the ladies and gentlemen from each RW in Sirnagalih Village. The socialization activities were divided into a number of events, ranging from the delivery of material to discussions with the people of Sirnagalih Village. The material presented in the form of potential yards that are important to be developed, types of plants that can be planted in the yard and how to plant it, examples of yards that are decorated for an effort to beautify parts of the house, and the benefits of joining the Yard Utilization Program. In addition, sketches were also made in the form of house plans and plots of land so that participants could draw plans for their use. During the socialization activities, the community seemed enthusiastic listening to the material and giving questions. Keywords: Land, Sirnagalih Village, socialization